Comparison study of quality control standards between private and public medical diagnostic laboratories in Shiraz- 2011 - MA Rezaei; F Ghahramani; GH Sadravi (Tehran University of Medical Sciences, 2012)
Background: Medical diagnostic laboratories play an important role in diagnosis, treatment and prevention of the diseases. Today's without assisting of the laboratories, conserving of public health and outbreaks prevention of infectious and genetic diseases is impossible. In this research the cases determined by the department of health and medical education questionnaire in quality control of public and private laboratories. Materials and Methods: This study is a cross sectional (descriptive and analytic) in which 20 private medical diagnostic laboratories and 16 training centers were selected. The quality control standards were reviewed and compared. Results: From 12 items of the questionnaire the two following items, rules and regulations in both private and public laboratories gained the highest priorities with 100% private and 93% governmental laboratories respectively. The lowest score was related to testing quality control of the laboratories with that of public and private ones, 82% and 75.7 percent respectively. In all that cases, governmental laboratories and training centers were rated lower than private labs. Conclusion: This study showed that both private and public laboratories' score were under below of standards. Governmental laboratories were rated lower than private labs. In private laboratories, identifying errors and in the governmental laboratories, testing quality control should be considered